Contribution of occult precipitation to the water balance of páramo ecosystems in the Colombian Andes. Issue 24 (7th November 2017) - Cárdenas, Maria Fernanda; Tobón, Conrado; Buytaert, Wouter
Abstract: Páramos are high‐altitudinal neotropical ecosystems located in the upper regions of the northern Andes. Their hydrology is characterized by an extraordinarily high run‐off ratio. One major contributing mechanism is thought to be fog occurrence, which is common in the páramos and occurs by the cooling of near‐surface moist air, as it is forced to higher elevations by topography. However, field‐based observations and quantification of this flux are rare. We present results of monitoring of occult precipitation, understood as the combination of fog and drizzle inputs, combined with meteorological and soil moisture monitoring for periods between 7 to 17 months in 6 sites distributed over 3 páramos catchments in Colombia: three sites in Romerales (Quindío), two in Chingaza (Cundinamarca), and one in Belmira (Antioquia). Occult precipitation inputs were measured with cylindrical fog gauges with a cover on top. We estimate occult precipitation inputs to add between 7% and 28% to rainfall inputs in the study sites. Our results also show that occult precipitation has a large temporal and spatial variability, both within one site and between sites, which make it difficult to upscale and quantify at a catchment scale. Nevertheless, occult precipitation can be important for downstream water supply given that these inputs are especially concentrated during periods with low rainfall. Lastly, we also find evidence for an increase in soil moisture related to occult precipitation during a dry period in Romerales páramo.